2020
DOI: 10.1002/ps.5747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 and temperature on survival and wing dimorphism of two species of rice planthoppers (Hemiptera: Delphacidae) under interaction

Abstract: BACKGROUND: Anthropogenic climate change (ACC) may have significant impacts on insect herbivore communities including pests. Two of the most important climate-change related factors are increased atmospheric concentrations of carbon dioxide (CO 2 ), and increasing mean global temperature. Although increasing attention is being paid to the biological and ecological effects of ACC, important processes such as interspecific interaction between insect herbivores have been little explored. Here, in a field experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Under the current global climate change, arthropods in rice fields are adapting to this change in various ways (Heong et al., 1995), such as BPH. Studies focused on how global climate change affects development and fecundity of BPH (Jeong et al., 2020; Liu et al., 2020; Wan, Dang, et al., 2014; Wang et al., 2020). However, few researches have reported the effects of hormones on the growth and development of BPH at elevated CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Under the current global climate change, arthropods in rice fields are adapting to this change in various ways (Heong et al., 1995), such as BPH. Studies focused on how global climate change affects development and fecundity of BPH (Jeong et al., 2020; Liu et al., 2020; Wan, Dang, et al., 2014; Wang et al., 2020). However, few researches have reported the effects of hormones on the growth and development of BPH at elevated CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have shown that changes in climate can alter the outcomes of interactions between competing herbivores to affect herbivore community structure and the composition of plant communities (Lin et al., 2018; Ntiri et al. 2016; Schädler et al., 2007; Sun et al., 2009; Wang et al., 2018; Wang et al., 2020). Much of this previous research on the nature of temperature‐dependent interspecific interactions between herbivorous insects has focused primarily on interspecific competition for resources without assessing the effects of temperature on positive or negative interspecific interactions as mediated through plant defence pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Some detailed multi-trophic studies have been conducted to elucidate the potential effects of elevated temperatures and other changes in climate on the population dynamics of phloem feeders and on their impacts on host plants, including crops (Barton & Ives, 2014;Han et al, 2019;Meisner et al, 2014). Such studies have shown that changes in climate can alter the outcomes of interactions between competing herbivores to affect herbivore community structure and the composition of plant communities (Lin et al, 2018;Ntiri et al 2016;Schädler et al, 2007;Sun et al, 2009;Wang et al, 2018;Wang et al, 2020). Much of this previous research on the nature of temperature-dependent interspecific interactions between herbivorous insects has focused primarily on interspecific competition for resources without assessing the effects of temperature on positive or negative interspecific interactions as mediated through plant defence pathways.…”
Section: Introductionmentioning
confidence: 99%